Framing Analysis of Road Damage News in Bengkulu Province on Media TribunBengkulu.com (Period October 2023-March 2024 - Aldira, Erike; Hafizah, Evi; Sari, Eka Vuspa; Marlina, Neneng Cucu (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The media, in constructing the reality of problems in the news, certainly has their own point of view. Media content is not a reflection of the reality of what is actually happening, but has been formed by the media itself with the background of the ideology and interests of the media concerned. This research aims to analyze how infrastructure damage in mass media news with an emphasis on aspects of public interest. Through the framing analysis approach, this research tries to examine the way the mass media frames the issue of road damage, including the causal factors, the impact felt by the community, and the proposed solutions. The research method used is a qualitative method to analyze news articles related to road damage in Bengkulu Province from the media source TribunBengkulu.com. Several news articles were analyzed to identify the framing patterns used by the media. The results showed that TribunBengkulu.com tends to highlight road damage in Bengkulu Province as a significant problem for people's daily lives, with an emphasis on the importance of immediate repairs and the responsibility of the local government. The implications of these findings are the need for framing that takes into account the interests of the public in presenting accurate and relevant information about road damage, as well as the importance of an honest and fair role of the media in building awareness and support.